La campana sommersa = The sunken bell - Respighi, Ottorino 1879-1936 (Naxos Right (Europe) Ltd., 2018)
A symbolist drama on a supernatural theme, it is steeped in beauty, mystery and foreboding, and orchestrated with the Romantic opulence familiar from his sumptuous trilogy of Roman tone poems
Interpreten unter anderem: Valentina Farcas (Rautendelein). Maria Luigia Borsi (Magda). Angelo Villari (Enrico). Thomas Gazheli (The Ondino). Orchestra del Teatro lirico di Cagliari. Coro del Teatro lirico di Cagliari. Donato Renzetti (Dirigent)
Aufnahme: Teatro Lirico di Cagliari, 30. März bis 1. April 2016
Includes program notes by Attilio Piovano and Potito Pedarra and biographical information on the performers in English and Italian (19 pages: portraits) inserted in container
Bildformat: 16:9
Keywords: Operas; Filmed operas; Film; Blu-Ray-Disc